LATENT COGNITIVE PATTERNS OF HUMOUR: A NEW APPROACH TO EXPLAINING CREATION AND MEANING OF HUMOUR - Radojica (Rade) Bojanović (Istraživanja u Pedagogiji)
Three great theories of humour aspire to summarize the meaning of humour into one formula. Since humour is a complex phenomenon, with a number of different forms, it is necessary to analyze a number of humour patterns in order to create a more reliable base for defining the meaning of humour. We have started from the concept of basic jokes. These are patterns based on which humourists write a great number of jokes, graffiti, and aphorisms. However, humourists and humour theoreticians have not defined basic jokes. They are usually not on the conscious level. That is why we named them latent cognitive patterns of humour. In this paper, we have defined 24 cognitive patterns of humour. Then, we have demonstrated how the jokes from the same series can be written based on these cognitive patterns. Finally, this confirmed by an empirical test.